1979
DOI: 10.1017/s0021859600037989
|View full text |Cite
|
Sign up to set email alerts
|

The growth and development of cowpeas (Vigna unguiculata)under tropical field conditions: 2. Accumulation and partition of dry weight

Abstract: SUMMARYThe pattern of dry weight accumulation and partition of cowpea crops grown in Nigeria is described. For the first 50 days, increase in dry matter was proportional to intercepted radiation. Differences in dry weight between crops were due equally to variations in incident solar radiation, the fraction of this radiation intercepted, and the efficiency with which it was used. The variation in total pod weight from 206 to 312 g/ma resulted from differences in number of pods, mean pod weight being constant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 12 publications
6
12
0
2
Order By: Relevance
“…73 g/MJ for two different sowing dates corresponding to rainfed and drought conditions. In optimal conditions, the RUE in cowpeas is c. 1 g/MJ (Littleton et al 1979;Muchow et al 1993;Craufurd & Wheeler 1999), which is similar to maximum values reported for other tropical grain legumes (0 . 9-1 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…73 g/MJ for two different sowing dates corresponding to rainfed and drought conditions. In optimal conditions, the RUE in cowpeas is c. 1 g/MJ (Littleton et al 1979;Muchow et al 1993;Craufurd & Wheeler 1999), which is similar to maximum values reported for other tropical grain legumes (0 . 9-1 .…”
Section: Discussionsupporting
confidence: 83%
“…Functional growth analyses (FGA) can delineate quantitatively the productive capacity of plant communities in terms of allometric indices such as the morphogenetic indicators of yield and harvesting (Sˇesta´k et al 1971). In the case of cowpea, FGA has been carried out by Ojehomon (1970), Adepetu & Akapa (1977), Littleton et al (1979), Ferna´ndez & Miller (1985 and Lawn (1989). The simultaneous analysis of the environmental effect on production and the genetic dependence on yielding capacity has usually been carried out under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(15.1 kg seed ha-1 day-1 ). However, the mean crop growth rate of 1.26g m-2 day-1 and growth duration of 176 days observed in this study, compared woefully with average crop growth rate of 6.8-11.2g m-2 day-1 and a growth duration of 52 days obtained for cowpea, under similar tropical conditions (Littleton et al, 1979). Ruinard (1989) has also reported disappointing vegetative growth of jackbean on the low-fertility, acid sandy soils of Surinane's Zanderij belt.…”
Section: Discussionsupporting
confidence: 52%
“…The e for cowpea (0.47 and 0.79 g MJ ) and hlackgrarn (0.64 and 0.81 g MF' ) are within the lower range of previously reported values for pulse crops (Littleton et al. 1979: Muchow.…”
Section: )supporting
confidence: 83%